2020
DOI: 10.1093/jn/nxaa258
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum 25-Hydroxyvitamin D Deficiency with Risk of Incidence of Disability in Basic Activities of Daily Living in Adults >50 Years of Age

Abstract: Background Vitamin D deficiency compromises muscle function and is related to the etiology of several clinical conditions that can contribute to the development of disability. However, there are few epidemiological studies investigating the association between vitamin D deficiency and the incidence of disability. Objectives We aimed to assess whether vitamin D deficiency is associated with the incidence of disability in basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Moreover, the risk of basic activities of daily living (BADL) disability is related to vitamin D deficiency in both sexes; however, in females, this risk is much higher (53% vs. 44%) (69). In addition, a greater risk of female skeletal abnormalities associated with vitamin D deficiency was confirmed by a study on so-called residual rickets.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the risk of basic activities of daily living (BADL) disability is related to vitamin D deficiency in both sexes; however, in females, this risk is much higher (53% vs. 44%) (69). In addition, a greater risk of female skeletal abnormalities associated with vitamin D deficiency was confirmed by a study on so-called residual rickets.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Osteoporosis and osteopenia were found in as many as 91% of women with PD, while in the group of men with PD, the same diseases were present in 61% of respondents (66). Interesting information is provided by a case study that searched for differences in the type of hip fracture in relation to 25 Further, a UK cross-sectional study, using data from the English Longitudinal Study of Aging (ELSA) and conducted with people over 50 years old, demonstrated that a higher plasma concentration of 25(OH)D lowers the risk of disability in women, but not in men (69).…”
Section: 1skeletal and Muscle Disordersmentioning
confidence: 99%
“…Serum 25(OH)D concentrations were analyzed in the Royal Victoria Infirmary (Newcastle upon Tyne, United Kingdom) by DiaSorin Liaison immunoassay, which provides the total circulating 25(OH)D concentrations and has an analytical sensitivity of 7.5 nmol/L, with a variation coefficient ranging from 8.7% to 9.4%. All assays were performed in duplicate, and the laboratory that performed the 25(OH)D analyses participated in the Vitamin D External Quality Assessment Schemes (DEQAS) [ 25 ]. According to the Institute of Medicine, serum 25(OH)D concentrations were classified as: sufficient (>50 nmol/L), insufficient (>30 and ≤50 nmol/L) and deficient (≤30 nmol/L) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The socioeconomic characteristics included age (grouped into five 10-year categories as 50–59; 60–69; 70–79; 80–89 and 90 or more), race (white and non-white), conjugal life (with or without), schooling (>13 years; 12–13 years; ≤11 years) and total household wealth classified in quintiles [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation